Exposure as part of a systems approach for assessing risk. - Sheldon LS; Hubal EAC (Environmental Health Perspectives, 2009)
BACKGROUND: The U.S. Environmental Protection Agency is facing large challenges in managing environmental chemicals with increasingly complex requirements for assessing risk that push the limits of our current approaches. To address some of these challenges, the National Research Council (NRC) developed a new vision for toxicity testing. Although the report focused only on toxicity testing, it recognized that exposure science will play a crucial role in a new risk-based framework. OBJECTIVE: In this commentary we expand on the important role of exposure science in a fully integrated system for risk assessment. We also elaborate on the exposure research needed to achieve this vision. DISCUSSION: Exposure science, when applied in an integrated systems approach for risk assessment, can be used to inform and prioritize toxicity testing, describe risks, and verify the outcomes of testing. Exposure research in several areas will be needed to achieve the NRC vision. For example, models are needed to screen chemicals based on exposure. Exposure, dose-response, and biological pathway models must be developed and linked. Advanced computational approaches are required for dose reconstruction. Monitoring methods are needed that easily measure exposure, internal dose, susceptibility, and biological outcome. Finally, population monitoring studies are needed to interpret toxicity test results in terms of real-world risk. CONCLUSION: This commentary is a call for the exposure community to step up to the challenge by developing a predictive science with the knowledge and tools for moving into the 21st century.